Fatores socioculturais facilitadores do processo orçamentário eficaz nas organizações - Livovschi, Flavio Roberto (2013)
The main purpose of this survey is to determine the possible sociocultural factors that facilitate the institutionalization of an efficient budgeting process at organizations. Additionally, this survey also sought to analyze the inputs of respondents and their perceptions of the sociocultural factors that affect the institutionalization of the budgeting process. The empirical survey was produced as a questionnaire answered by managers of Strategic Planning and Controller s departments, or their peers, who are responsible for the budgeting process, in the form of a non-probabilistic sample, which supplied data on the possible sociocultural factors that facilitate the institutionalization of the budgeting process. According to the respondents, the combination of many factors, such as hierarchization, cultural values, cultural level, commitment of those involved, demographic factors, and organizational culture, all influence the occurrence of organizational changes. The level of involvement of the respondents was essential for the quality of the answers. For 76% of the respondents, the efficient budgeting process, once it was institutionalized at the organizations, improved the quality and efficiency of management, bringing further control and generating economic results; 66% of the organizations have been adopting the budget management model for more than three years. Regarding the critical success factors, such as the existence of a formal document, good communication of the plan, the inclusion of the budgeting process in the planning process and the management of the budgeting process by the Controller s Department, 50% of respondents agreed that all these factors are relevant for the implementation of the budget; the remaining 50% suggest different combinations of factors. We consider that the purpose of the survey was achieved and the main sociocultural factors mentioned by the respondents were: hierarchization, with 52%, and social values, related to cultural level, commitment and proactivity of those involved, with 18%